Book Review - Charlotte Schwennsen (Names, 2024)
The Wordhord: Daily Life in Old English. By Hana Videen. Princeton: Princeton University Press.  2022. Pp. 296. (Paperback) $23.95. ISBN 13: 9780691232744.